Anxiety and depressive symptoms and coping strategies in Nasopharyngeal carcinoma patients in Hospital Kuala Lumpur - Naing @ Noor Jan, Khin Ohnmar; Abdul Aziz, Nor Azillah; Ismail, Nooriny; Tan, C. H.; Yap, Yoke Yeow; Awang, Hamidin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Introduction: Nasopharyngeal Carcinoma (NPC) is the second most common cancer among men in Malaysia. Establishing local data will help to improve the treatment strategies and lower the anxiety and depression level among NPC patients. Our aim was to compare the level of symptoms of anxiety and depression and the coping strategies employed between NPC and cancer-free patients. Methods: A comparative cross-sectional study with universal sampling was conducted on 22 NPC patients and 30 cancer-free patients from the Oncology and Radiotherapy Department and Ear, Nose and Throat clinic of Hospital Kuala Lumpur (HKL) between 12 to 29 May 2008. In this study, the symptoms of depression and anxiety were obtained by using the Hospital Anxiety and Depression Scale (HADS) while Brief COPE questionnaire was used to understand patients’ coping strategies. Results: The prevalence of NPC was higher in the Chinese, men, aged between 40 and 59 years, and those from the lower income group. The levels of anxiety and depression symptoms were found to be higher in the NPC group as compared to the cancer-free group. However, only the level of depression was found significantly related to the NPC group (p=0.002). This study also found that the two comparison groups were using different types of coping strategies. The NPC patients mainly used ‘acceptance’ as their coping strategy while the comparative group most often used ‘religion’. Among the types of coping strategies reported by the patients, ‘use of instrumental support’ type was found to be associated with a lower level of anxiety (p = 0.035) and ‘humour’ type was associated with lower depressive symptoms (p = 0.269). On the contrary, ‘selfblame’ type was associated with both anxiety (p =0.0001) and depression (p = 0.001) symptoms. In addition, patients with different gender, ethnicity, educational levels, and monthly income were also found to have significant differences in their levels of anxiety and depression as well as type of coping strategies. Conclusions: NPC patients had higher anxiety and depression levels as compared to the comparative group. Different socio-demographic backgrounds and different types of coping strategies had an influence on patients resulting in different levels of anxiety and depression.